When empirical data challenge entrenched interpretations: Revisiting the “hyaenid metanarrative” at Fuente Nueva 3 archaeological site (Orce, Granada, Spain) - José Yravedra; Lloyd A. Courtenay; Mario Gutiérrez-Rodríguez; Juan Francisco Reinoso-Gordo; Juha Saarinen; Natalia Égüez; Carmen Luzón; Juan José Rodríguez-Alba; Stefania Titton; Eva Montilla-Jiménez; José Cámara-Donoso; Darío Herranz-Rodrigo; et al. (Quaternary Science Reviews, 2026)

Coastal barchanoid dunes differentiation and evolution model: Cap Ferret Spit, Aquitaine Coast France - Clelia Billières-Kim; Julie Billy; Raphaël Bourillot; Hugues Féniès; Alexandre Nicolae Lerma (Geomorphology, 2026)

Coupled abiotic-biotic processes driving manganese removal in a pozzolona biofilter of a full-scale passive mine water treatment plant - Charlotte Lafont; Stéphane Vaxelaire; Alexandre Gelabert; Catherine Joulian; Hugues Thouin; Frédéric Duré; Mickael Charron; Delphine Vantelon; Fabienne Battaglia-Brunet; Éric D. van Hullebusch (Water Research, 2026)

Protocol development for an efficient digitization of palaeontological heritage: The case of Camp dels Ninots fossil site (Spain) - Adriana Linares-Martín; Bruno Gómez de Soler; Roy M. Farman; Elena Moreno-Ribas; Pablo Mateos Prieto; Marta Fontanals; Andrea Alías; Javier Sopesens; Hugues-Alexandre Blain; Gerard Campeny Vall-llosera (Geoheritage, 2026)

Manganese removal in a full-scale constructed wetland for passive mine water treatment: Environmental factors and microbial communities - Charlotte Lafont; Stéphane Vaxelaire; Alexandre Gelabert; Catherine Joulian; Hugues Thouin; Frédéric Duré; Mickael Charron; Josselin Gorny; Delphine Vantelon; Fabienne Battaglia-Brunet; Éric D. van Hullebusch (Water Research, 2026)

Influences of seasonal prey availability and anthropogenic landscape on small-vertebrate based palaeoecological reconstructions: a case study from the mid-late Holocene transition at El Mirador cave (Sierra de Atapuerca, Spain) - Josep Francesc Bisbal-Chinesta; Hugues-Alexandre Blain; Sandra Bañuls-Cardona; Iván Rey-Rodríguez; Carmen Núñez Lahuerta; Ethel Allué; Isabel Expósito; Gloria Cuenca-Bescós; Josep Maria Vergès (Quaternary International, 2026)

Neotaphonomic insights from modern owl pellets in the Ararat Depression (Armenia): Implications for Middle Paleolithic microvertebrate accumulations - Dominik L. Rogall; Hugues-Alexandre Blain; Tsovinar Hovhannisyan; Andranik Gyonjyan; Gor Kaloyan; Boris Gasprayan; Ariel Malinsky-Buller (Archaeological and Anthropological Sciences, 2026)
Predator-accumulated microvertebrate assemblages preserve high-resolution records of past ecosystems, yet their interpretation requires robust modern analogues. Here, we present the first neotaphonomic study of owl pellets from the Ararat Depression (Armenia), a key biogeographic corridor of the Armenian Highlands. By comparing modern prey assemblages accumulated by the Eurasian Eagle-owl ( Bubo bubo ) and the Little Owl ( Athene noctua ), we evaluate predator-specific taphonomic signatures and their implications for interpreting Middle Paleolithic microfaunal deposits. Taxonomic, skeletal, and digestive data were quantified. Results show clear distinctions between B. bubo and A. noctua accumulations in prey spectrum, fragmentation, and digestion intensity, with (A) noctua producing highly fragmented and prey-restricted assemblages, and (B) bubo yielding more diverse and less altered remains. These taphonomic results are then utilized to evaluate environmental indices (Taxonomic Habitat Index, Habitat Weighting Method) in order to reconstruct prey habitats. Application of these modern analogues to Holocene and late Pleistocene deposits at Ararat-1 Cave and Kalavan-2 reveals that A. noctua is a potential accumulator at Ararat-1 during the Holocene, while mixed signals at Ararat-1 Cave and Kalavan-2 open-air site during the Pleistocene suggest additional taphonomic agents. Importantly, the owl-derived faunal signal consistently indicates open steppe–shrubland environments with only limited woodland cover. This refines previous, more general environmental reconstructions by providing a taxon-specific, predator-mediated perspective on local habitats at the scale of human occupation, a line of evidence that has not previously been applied in the Armenian Highlands. Together, these results establish a foundational neotaphonomic framework for the region and demonstrate how modern owl assemblages can refine archaeological interpretations and paleoenvironmental reconstructions.

Chronological, paleoclimatic, and paleoenvironmental data from Łabajowa Cave (Kraków-Częstochowa Upland, Poland): a comprehensive approach for investigating a complex Late Pleistocene sequence - Claudio Berto; Mateusz Baca; Helen Fewlass; Greta Brancaleoni; Hugues-Alexandre Blain; Angel Blanco-Lapaz; Barbara Bujalska; Maciej T. Krajcarz; Aleksandra Kropczyk; Adrian Marciszak; Magdalena Moskal del Hoyo; Andrea Pereswiet Soltan; et al. (Quaternary Science Reviews, 2026)

The local paleoenvironment of Kalavan‐2 based on small‐vertebrate remains and its implications for human‐environment‐dynamics between 60 and 35 ka in the Armenian Highlands - Dominik L. Rogall; Monika V. Knul; Hugues‐Alexandre Blain; Boris Gasparyan; Ariel Malinsky‐Buller (Journal of Quaternary Science, 2026)
Kalavan‐2, a high‐altitude (∼1640 m a.s.l.) open‐air site in Armenia, preserves stratified Middle Paleolithic occupations with a rich small‐vertebrate record. Luminescence dating has placed site formation between ~60 and 45 ka, but without independent chronological control of the microvertebrate accumulation. Here, we apply accelerator mass spectrometry (AMS) 14 C dating directly to individual rodent bones, made possible by recent advances in collagen extraction. These new radiocarbon ages refine the chronology to late marine isotope stage 3 (ca. 50–35 ka), in agreement with luminescence estimates. In addition, we conducted detailed taphonomic and taxonomic analyses of the microvertebrates, alongside paleoenvironmental reconstruction using the Taxonomic Habitat Index and Habitat Weighting Method. The microfaunal assemblage, dominated by cold‐adapted rodents and insectivores, indicates open, montane steppe conditions during occupation, contrasting with today's mixed forest. Combined chronological and faunal evidence suggests episodic high‐altitude hunting by Late Pleistocene hunter‐gatherers, consistent with models of seasonal mobility. More broadly, this study demonstrates the potential of direct 14 C dating on microvertebrate remains to independently anchor Paleolithic chronologies and strengthen reconstructions of human adaptations in marginal environments.

Paleoecological context of Homo aff. erectus (ATE7-1) at Sima del Elefante (late Early Pleistocene, Atapuerca, Spain) inferred from the herpetofaunal assemblage - Christian Sánchez-Bandera; Ana Fagoaga; Hugues-Alexandre Blain; Juan Manuel López-García; Carmen Núñez-Lahuerta; Àngel Blanco-Lapaz; Julia Galán; Raquel Moya-Costa; Gloria Cuenca-Bescós; Xosé Pedro Rodríguez-Álvarez; Rosa Huguet (Journal of Human Evolution, 2025)

New palaeoecological insights for the early human occupation in Europe: amphibians and reptiles from the Early Pleistocene of Pirro Nord 13 (Apricena, southern Italy) - Christian Sánchez-Bandera; Hugues-Alexandre Blain; Josep Francesc Bisbal-Chinesta; Ana Fagoaga; Marco Pavia; Massimo Delfino (Quaternary Science Reviews, 2025)

Comparing past and present. The Holocene and Marine Isotope Stage 3 microvertebrate assemblage of Ararat-1 Cave, Armenia - Dominik L. Rogall; Hugues-Alexandre Blain; Ioannis A.K. Oikonomou; Theodoros Karampaglidis; Artur Petrosyan; Boris Gasparyan; Ariel Malinsky-Buller (Quaternary Science Reviews, 2025)

New paleoecological insights for the Late Pleistocene Neanderthal mountain occurrence at Buena Pinta Cave (Iberian Central System, Pinilla-del-Valle, Madrid, Spain) - Hugues-Alexandre Blain; César Laplana; Christian Sánchez-Bandera; Clara Mielgo; Ángel Blanco-Lapaz; Rafael Marquina-Blasco; Ana Fagoaga; Josep Francesc Bisbal-Chinesta; David Manuel Martín-Perea; Christophe Falguères; Tom Higham; Maria Blanca Ruiz Zapata; et al. (Quaternary Science Reviews, 2025)

The squat jump and sprint force–velocity profiles of elite female football players are not influenced by the menstrual cycle phases and oral contraceptive use - Jérémie Bouvier; Pierre-Hugues Igonin; Mélanie Boithias; Alexandre Fouré; Alain Belli; Nathalie Boisseau; Cyril Martin (European Journal of Applied Physiology, 2025)

Rainiest Spain: amphibians and reptiles from the late Early Pleistocene-age site of El Chaparral (Cádiz) - Christian Sánchez-Bandera; Rafael Marquina Blasco; Josep Francesc Bisbal-Chinesta; Ana Fagoaga; Isabel Cáceres; José María Gutiérrez; Francisco Giles Pacheco; Juan Manuel López-García; Hugues-Alexandre Blain (Palaeobiodiversity and Palaeoenvironments, 2025)

Palaeoecological characterization of the Pliocene-Pleistocene transition on the Mediterranean littoral area: Almenara-Casablanca (Castellón, eastern Spain) - Rafael Marquina-Blasco; Christian Sánchez-Bandera; Juan Manuel López-García; Alberto Martínez-Ortí; Paloma Sevilla; Francisco Javier Ruiz-Sánchez; Hugues-Alexandre Blain (Quaternary Science Reviews, 2025)

Genome-wide analyses provide insights into genetic variation, phylo- and co-phylogenetic relationships, and biogeography of the entomopathogenic nematode genus Heterorhabditis - Ricardo A.R. Machado; Arthur Muller; Alexandre Hiltmann; Aashaq Hussain Bhat; Vladimír Půža; Antoinette P. Malan; Carlos Castaneda-Alvarez; Ernesto San-Blas; Larry W. Duncan; David Shapiro-Ilan; Javad Karimi; Lalramliana; et al. (Molecular Phylogenetics and Evolution, 2025)

A revisit to the Early Pliocene site of Abla (Guadix-Baza Basin, southern Spain) - Pedro Piñero; Jordi Agustí; Hugues-Alexandre Blain; María Teresa Alberdi; Ángel Blanco Lapaz; Marc Furió (Geobios, 2024)

Not seen before. Unveiling depositional context and Mammuthus meridionalis exploitation at Fuente Nueva 3 (Orce, southern Iberia) through taphonomy and microstratigraphy - José Yravedra; Lloyd A. Courtenay; Mario Gutiérrez-Rodríguez; Juan Francisco Reinoso-Gordo; Juha Saarinen; Natalia Égüez; Carmen Luzón; Juan José Rodríguez-Alba; José A. Solano; Stefania Titton; Eva Montilla-Jiménez; José Cámara-Donoso; et al. (Quaternary Science Reviews, 2024)

Environmental and climatic inferences for Marine Isotope Stage 2 of southern Belgium (Meuse valley, Namur Province) based on rodent assemblages - Juan Manuel López-García; Hugues-Alexandre Blain; Quentin Goffette; Cécila Cousin; Annelise Folie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Small vertebrates from the Late Pliocene Las Higueruelas locality of central Spain with new biochronological and palaeoecological inferences - Hugues-Alexandre Blain; Tomáš Přikryl; Pedro Piñero; Christian Sánchez-Bandera; Almudena Martínez-Monzón; Ana Fagoaga (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Multiproxy approach to reconstruct the climate and environment of a new late Middle Pleistocene vertebrate site in northwestern Italy - Pedro Piñero; Juan Manuel López-García; Hugues-Alexandre Blain; Giorgio Carnevale; Marc Furió; Piero Giuntelli; Elisa Luzi; Loredana Macaluso; Giuseppe Marramà; Shubham Pal; Giulio Pavia; Marco Pavia; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Glacial/interglacial climate variability in southern Spain during the late Early Pleistocene and climate backdrop for early Homo in Europe - Christian Sánchez-Bandera; Ana Fagoaga; Alexia Serrano-Ramos; José Solano-García; Deborah Barsky; Daniel DeMiguel; Juan Ochando; Juha Saarinen; Pedro Piñero; Iván Lozano-Fernández; Lloyd A. Courtenay; Stefania Titton; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Redefining the MIS 3 climatic scenario for Neanderthals in northeastern Iberia: A multi-method approach - Ana Fagoaga; Mónica Fernández-García; Juan Manuel López-García; M. Gema Chacón; Palmira Saladié; Josep Vallverdú; Francisco Javier Ruiz-Sánchez; Hugues-Alexandre Blain (Quaternary Science Reviews, 2023)

To den or not to den. Contributions to the taphonomic history of the Early Pleistocene site of Venta Micena 4 (Orce, Guadix-Baza Basin) - Jose Yravedra Sainz de los Terreros; Carmen Luzón; Jose A. Solano; Gonzalo J. Linares-Matas; Verónica Estaca-Gomez; Juan José Rodríguez-Alba; Lloyd A. Courtenay; Darío Herranz-Rodrigo; Alexia Serrano-Ramos; José Cámara; Juha Saarinen; Christian Sánchez-Bandera; et al. (Quaternary Science Reviews, 2023)

Building the information system of the French Critical Zone Observatories network: Theia/OZCAR-IS - Isabelle Braud; Véronique Chaffard; Charly Coussot; Sylvie Galle; Patrick Juen; Hugues Alexandre; Philippe Baillion; Annick Battais; Brice Boudevillain; Flora Branger; Guillaume Brissebrat; Rémi Cailletaud; et al. (Hydrological Sciences Journal, 2022)

Microvertebrate studies in archaeological contexts: Middle Paleolithic to early Holocene past environments - Juan Manuel López-García; Hugues-Alexandre Blain; Sara E. Rhodes; Ángel Blanco-Lapaz (Archaeological and Anthropological Sciences, 2022)

New paleoecological perspectives on Late Pleistocene Neanderthals in northern Balkans: the rodent assemblages from Smolućka cave (Serbia) - Mihailo Jovanović; Katarina Bogićević; Draženko Nenadić; Jordi Agustí; Christian Sánchez-Bandera; Juan Manuel López-García; Hugues-Alexandre Blain (Archaeological and Anthropological Sciences, 2022)
During the Late Pleistocene, the Balkans came to be an important region with many isolated areas, enabling fauna, alongside Neanderthals, to thrive in the area. This work is focused on paleoenvironmental and paleoclimatic changes that occurred in the northern Balkan Peninsula with a special focus on fossil record from Smolućka cave aging from MIS 5 to MIS 3. Based on available data, an attempt has been made to establish a synthetic chronological context for the faunal assemblages recovered from Smolućka cave. Tentative attribution of layer 5 to MIS 5 relies on the interstadial pattern of our reconstructions, with favorable climate conditions for a large diversity of species and with mean annual temperature (MAT) reaching up to 3 °C higher than present values and abundant rainfall in the area. Cold conditions for MIS 4 are not present in Smolućka, although layer 4 (late MIS 5 or early MIS 4) shows somewhat dryer and cooler climate when compared with other layers. Layers 3z and 3 (MIS 3) are characterized by temperate and humid conditions together with a complex system of mosaic habitats with high environmental heterogeny but generally favorable conditions for a large diversity of life. Although still not fully chronologically constrained, Smolućka cave presents an interesting opportunity for future research, in the time period when only Neanderthals occupied the Balkans and thrived in local conditions. The transition between the Neanderthals and anatomically modern humans has not yet been established but can be expected in future research.

Applying the UDA-ODA discrimination technique to a herpetological association: the case of the Middle Palaeolithic site of El Salt (Alcoi, Spain) - Rafael Marquina-Blasco; Ana Fagoaga; Vicente D. Crespo; Salvador Bailon; Carolina Mallol; Cristo M. Hernández; Bertila Galván; Hugues-Alexandre Blain; Francisco Javier Ruiz-Sánchez (Archaeological and Anthropological Sciences, 2022)
El Salt (Middle Palaeolithic; Alcoi, Spain) is a key site for understanding the disappearance of Neanderthals in the eastern Iberian Peninsula, a process that is observed along its stratigraphic sequence. To improve our understanding of the palaeoclimatic context in which this process took place, we applied the UDA-ODA discrimination technique to the fossil herpetological assemblages from Stratigraphic Units (SU) Xb (52.3 ± 4.6 ka) and V (45.2 ± 3.4/44.7 ± 3.4 ka). This method is based in the application of an ecological criterion, the maximum altitude of each species on each Iberian range, to discern and remove those areas that do not meet their ecological requirements (UDA) from those that do (ODA), which are included in its distribution from Atlases from which the common distribution species is going to be extracted. Results indicate the existence of an alternation between “cold and wet” moments with “warm and dry” ones, all of them in a more humid context than nowadays. Climate was slightly warmer than nowadays in SU Xb, whereas was cooler in SU V. Regarding MAP, our results show less variation between SUs than it has been provided by previous studies. These results do not fully agree with those provided by small mammals from the same SUs, which indicate an increase of the temperatures whereas rainfall experienced the contrary. These differences could be related with the wider distribution of the Iberian herpetofauna, and some differences in the applied ecological criterion. Furthermore, herpetofaunal palaeoclimatic reconstruction shows that the abandonment of the site by Neanderthals seems to have occurred during an arid phase.

Ecological and genomic vulnerability to climate change across native populations of Robusta coffee ( Coffea canephora ) - Rémi Tournebize; Leyli Borner; Stéphanie Manel; Christine N. Meynard; Yves Vigouroux; Dominique Crouzillat; Coralie Fournier; Mohamed Kassam; Patrick Descombes; Christine Tranchant‐Dubreuil; Hugues Parrinello; Catherine Kiwuka; et al. (Global Change Biology, 2022)
The assessment of population vulnerability under climate change is crucial for planning conservation as well as for ensuring food security. Coffea canephora is, in its native habitat, an understorey tree that is mainly distributed in the lowland rainforests of tropical Africa. Also known as Robusta, its commercial value constitutes a significant revenue for many human populations in tropical countries. Comparing ecological and genomic vulnerabilities within the species’ native range can provide valuable insights about habitat loss and the species’ adaptive potential, allowing to identify genotypes that may act as a resource for varietal improvement. By applying species distribution models, we assessed ecological vulnerability as the decrease in climatic suitability under future climatic conditions from 492 occurrences. We then quantified genomic vulnerability (or risk of maladaptation) as the allelic composition change required to keep pace with predicted climate change. Genomic vulnerability was estimated from genomic environmental correlations throughout the native range. Suitable habitat was predicted to diminish to half its size by 2050, with populations near coastlines and around the Congo River being the most vulnerable. Whole‐genome sequencing revealed 165 candidate SNPs associated with climatic adaptation in C. canephora , which were located in genes involved in plant response to biotic and abiotic stressors. Genomic vulnerability was higher for populations in West Africa and in the region at the border between DRC and Uganda. Despite an overall low correlation between genomic and ecological vulnerability at broad scale, these two components of vulnerability overlap spatially in ways that may become damaging. Genomic vulnerability was estimated to be 23% higher in populations where habitat will be lost in 2050 compared to regions where habitat will remain suitable. These results highlight how ecological and genomic vulnerabilities are relevant when planning on how to cope with climate change regarding an economically important species.

Correction to: Use of meat resources in the Early Pleistocene assemblages from Fuente Nueva 3 (Orce, Granada, Spain) - José Yravedra; José Antonio Solano; Lloyd A. Courtenay; Juha Saarinen; Gonzalo Linares‑Matás; Carmen Luzón; Alexia Serrano‑Ramos; Darío Herranz‑Rodrigo; José Miguel Cámara; Auxiliadora Ruiz; Stefania Titton; Juan José Rodríguez‑Alba; et al. (Archaeological and Anthropological Sciences, 2022)

The last interglacial-glacial cycle in the Meuse Valley (southern Belgium) inferred from the amphibian and reptile assemblages: implications for Neanderthals and anatomically modern humans - Hugues-Alexandre Blain; Almudena Martínez Monzón; Josep-Francesc Bisbal-Chinesta; Juan Manuel López-García; Cécilia Cousin; Annelise Folie (Archaeological and Anthropological Sciences, 2022)

Use of meat resources in the Early Pleistocene assemblages from Fuente Nueva 3 (Orce, Granada, Spain) - José Yravedra; José Antonio Solano; Lloyd A. Courtenay; Juha Saarinen; Gonzalo Linares-Matás; Carmen Luzón; Alexia Serrano-Ramos; Darío Herranz-Rodrigo; José Miguel Cámara; Auxiliadora Ruiz; Stefania Titton; Juan José Rodríguez-Alba; et al. (Archaeological and Anthropological Sciences, 2021)
Over the last few decades, several types of evidence such as presence of hominin remains, lithic assemblages, and bones with anthropogenic surface modifications have demonstrated that early human communities inhabited the European subcontinent prior to the Jaramillo Subchron (1.07–0.98 Ma). While most studies have focused primarily on early European lithic technologies and raw material management, relatively little is known about food procurement strategies. While there is some evidence showing access to meat and other animal-based food resources, their mode of acquisition and associated butchery processes are still poorly understood. This paper presents a taphonomic and zooarchaeological analysis of the Fuente Nueva-3 (FN3) (Guadix-Baza, Spain) faunal assemblage, providing a more in-depth understanding of early hominin subsistence strategies in Europe. The present results show that hominins had access to the meat and marrow of a wide range of animal taxa, including elephants, hippopotami, and small- and medium-sized animals. At the same time, evidence of carnivore activity at the site suggests that these communities likely faced some degree of competition from large predators when acquiring and processing carcasses.

Oldowan stone knapping and percussive activities on a raw material reservoir deposit 1.4 million years ago at Barranco León (Orce, Spain) - Stefania Titton; Oriol Oms; Deborah Barsky; Amèlia Bargalló; Alexia Serrano-Ramos; José García-Solano; Christian Sánchez-Bandera; José Yravedra; Hugues-Alexandre Blain; Isidro Toro-Moyano; Juan Manuel Jiménez Arenas; Robert Sala-Ramos (Archaeological and Anthropological Sciences, 2021)

Early effects of temperate agroforestry practices on soil organic matter and microbial enzyme activity - Hugues Clivot; Caroline Petitjean; Nicolas Marron; Erwin Dallé; Julie Genestier; Nicolas Blaszczyk; Philippe Santenoise; Alexandre Laflotte; Séverine Piutti (Plant and Soil, 2020)

Integrating ecological and genetic structure to define management units for caribou in Eastern Canada - Glenn Yannic; Martin-Hugues St-Laurent; Joaquin Ortego; Joëlle Taillon; Alexandre Beauchemin; Louis Bernatchez; Christian Dussault; Steeve D. Côté (Conservation Genetics, 2016)

First record of Pelobates syriacus (Anura, Amphibia) in the early Pleistocene of Italy - Hugues-Alexandre Blain; Massimo Delfino; Claudio Berto; Marta Arzarello (Palaeobiodiversity and Palaeoenvironments, 2016)

The continental record of Marine Isotope Stage 11 (Middle Pleistocene) on the Iberian Peninsula characterized by herpetofaunal assemblages - Hugues‐Alexandre Blain; Iván Lozano‐Fernández; Andreu Ollé; Jesus Rodríguez; Manuel Santonja; Alfredo Pérez‐González (Journal of Quaternary Science, 2015)
Marine Isotope Stage (MIS) 11 in Iberia is documented at three main Acheulean archaeological sites: Gran Dolina (Burgos, Atapuerca), Áridos‐1 (Madrid) and Ambrona (Soria). As the amphibians and reptiles recovered as fossils from these sites are not extinct and their ecology can be directly studied, mutual climatic range and habitat weighting methods have been applied to the herpetofaunal assemblages to estimate climatic and environmental parameters during MIS 11. Compared with today, mean annual temperature varies from +2.7 to +0.3 °C and mean annual precipitation varies from +311.7 to +74.4 mm, suggesting, in accordance with the numerical dates for each locality, a progressive decrease in temperature and rainfall from the fully interglacial conditions of MIS 11c to the end of MIS 11. The presence of woodland areas is also well substantiated throughout the duration of MIS 11, at least during the interglacial and interstadial periods.

Biochronological data inferred from the Early Pleistocene small mammals of the Barranc de la Boella site (Tarragona, north‐eastern Spain) - IVÁN LOZANO‐FERNÁNDEZ; SANDRA BAÑULS‐CARDONA; HUGUES‐ALEXANDRE BLAIN; JUAN MANUEL LÓPEZ‐GARCÍA; JOSEP VALLVERDÚ; JORDI AGUSTÍ; GLORIA CUENCA‐BESCÓS (Journal of Quaternary Science, 2014)
In 2007, remains of Mammuthus meridionalis and 334 lithic artefacts were recovered in level 2 of Barranc de la Boella. The presence of M. meridionalis allows us to assign an age older than 700 ka to this level, which represents one of the few sites of this age with palaeontological remains associated with lithic industry. It also enables us to shed light on questions pertaining to the chronology and the biogeography of the earliest European human settlements. In this paper, the small mammals from the Barranc de la Boella site are described for the first time, with special emphasis on the arvicolines. The presence of Victoriamys chalinei and Mimomys savini allows us to estimate the age of level 2. Level 2 of the Barranc de la Boella site ranges between the top of the Jaramillo subchron (0.99 Ma) and shortly after the Brunhes–Matuyama transition at 0.78 Ma, thus covering a time span of great importance for our knowledge of the earliest human occupations in Western Europe.

Early Pleistocene palaeoenvironments at the time of the Homo antecessor settlement in the Gran Dolina cave (Atapuerca, Spain) - HUGUES‐ALEXANDRE BLAIN; GLORIA CUENCA‐BESCÓS; FRANCESC BURJACHS; JUAN MANUEL LÓPEZ‐GARCÍA; IVÁN LOZANO‐FERNÁNDEZ; JORDI ROSELL (Journal of Quaternary Science, 2013)
Hominin remains unearthed from level TD6‐2 of Gran Dolina have been dated to slightly more than 0.8 Ma. Owing to the importance of this discovery, every effort is being made to reconstruct the environment where these hominins once lived. In this paper, the mutual climatic range and habitat weighting methods are applied to the herpetofaunal assemblages in order to estimate climatic and environmental parameters. TD6‐2 is thus characterized by a warm and humid climate. Mean annual temperature is estimated at 2.1°C higher than at present in Burgos, with a greater increase in temperature during summer (+3.1°C) than during winter (+1.4°C). Rainfall was more abundant than at present (+407.2 mm), occurring as at present principally during spring and autumn. Humid meadows and riparian woody habitats were common. The association between warm climatic conditions and the not fully developed forest suggests that the several episodes of high‐intensity occupation in TD6‐2 may correspond to a recolonization by Homo antecessor of the high inland plateaus of the Iberian Peninsula from the Mediterranean seashore, using the Ebro valley as a savannah‐type corridor after a cold glacial period. Copyright © 2013 John Wiley & Sons, Ltd.

A coastal reservoir of terrestrial resources for neanderthal populations in north‐eastern Iberia: palaeoenvironmental data inferred from the small‐vertebrate assemblage of Cova del Gegant, Sitges, Barcelona - Juan Manuel López‐García; Hugues‐Alexandre Blain; Montserrat Sanz; Joan Daura (Journal of Quaternary Science, 2012)
Coastal areas as reservoirs of resources for hominid groups have been widely studied in recent years. These areas combine marine with terrestrial and wetland resources and would have been optimum sites for hominids, including Neanderthals. This is the case with the Cova del Gegant, a cave that today opens directly onto the Mediterranean Sea and is located in the north‐eastern Iberian Peninsula. The geomorphological evolution of the Massis del Garraf has provided evidence that during the late Pleistocene there was a littoral platform between 8 and 13 km wide in front of the Cova del Gegant. Within this framework, the data derived from analysis of the small vertebrates and large mammals recovered from Cova del Gegant, including taxa currently absent from the Massis del Garraf, suggest that the landscape surrounding the cave provided a richer terrestrial ecosystem for Neanderthals than is available in this zone today. Analysis of the small‐vertebrate association from the cave reveals that the landscape surrounding the cave was dominated by woodland‐edge and open environments and that the climate was Mediterranean. The results have been compared with the only Iberian site with similar characteristics to the Cova del Gegant, Gorham's cave (southern Iberia, Gibraltar), revealing differences and similarities in the landscape and climate on the basis of the small‐mammal assemblages as well as the differences in the accessibility to terrestrial mammalian resources for the Neanderthal groups. The landscape and the climate were reasonably similar at the two sites, but the differences in the accessibility of resources for the Neanderthals are directly related to the location of the sites and the coastal position. Whereas the Cova del Gegant was on a route of mammal migration (between the Ebro Valley and France) suited for securing terrestrial resources, Gorham's cave is located on a small peninsula with a lower abundance of terrestrial mammal resources. This is probably why the Neanderthal groups at Gorham's cave exploited marine resources, whereas there is no evidence of marine resources having been exploited at Cova del Gegant, even though the seashore was nearby. Copyright © 2011 John Wiley & Sons, Ltd.

First fossil evidence of an “interglacial refugium” in the Pyrenean region - Juan Manuel López-García; Hugues-Alexandre Blain; Ethel Allué; Sandra Bañuls; Amelia Bargalló; Patricia Martín; Juan Ignacio Morales; Mireia Pedro; Anna Rodríguez; Alex Solé; F. Xavier Oms (The Science of Nature, 2010)